The external evocation and movement-related modulation of motor cortex inhibition in children and adolescents with Tourette syndrome – a TMS/EEG study - Schmidgen, Julia; Konrad, Kerstin; Roessner, Veit; Bender, Stephan (Frontiers in Neuroscience, 2023)
Objective: This study tested the reactivity of motor cortex inhibition to different intensities of external stimulation by transcranial magnetic stimulation (TMS) and its internal modulation during different motor states in children and adolescents with Tourette syndrome. Methods: TMS-evoked N100 served as an indirect measure of GABA-B receptor function which is related to GABA-B receptor function. Combined TMS/EEG was used to analyze the TMSevoked N100 component evoked by different stimulation intensities as well as during resting condition, movement preparation (contingent negative variation task) and movement execution. The study included 18 early adolescents with Tourette syndrome and 15 typically developing control subjects.Results: TMS-evoked N100 showed a less steep increase with increasing TMS intensity in Tourette syndrome together with less modulation (disinhibition) over the primary motor cortex during the motor states movement preparation and movement execution. Children with Tourette syndrome showed equally high N100 amplitudes at 110% resting motor threshold (RMT) intensity during resting condition and a parallel decline of RMT and N100 amplitude with increasing age as control subjects.Conclusion: Our study yields preliminary evidence that modulation of motor cortical inhibitory circuits, during external direct stimulation by different TMS intensities and during volitional movement preparation and execution is different in children and adolescents with Tourette syndrome compared to controls. These results suggest that a reduced resting motor cortical inhibitory "reserve" could contribute to the production of unwanted movements. Our findings are compatible with increased regulation of motor cortex excitability by perceptionaction binding in Tourette syndrome instead of top-down / motor regulation and need to be replicated in further studies.